Scanning electro-chemical microscopy reveals cancer cell redox state. (10th October 2015) - Rapino, Stefania; Marcu, Raluca; Bigi, Alessandra; Soldà, Alice; Marcaccio, Massimo; Paolucci, Francesco; Pelicci, Pier Giuseppe; Giorgio, Marco
Graphical abstract: Abstract: Cancer cells show an abnormal balance of reduced/oxidised species and the detection of cancer redox balance can be exploited for diagnostic purposes. In particular, it is known that the expression of oncogenic Ras changes the intracellular oxidised/reduced glutathione balance. Electrochemical imaging of living cells is currently feasible by scanning electrochemical microscopy and was used here, using ferrocenemethanol as redox mediator, to measure the oxidised/reduced glutathione balance in human breast epithelial MCF10A cells expressing constitutively active Ha-Ras Val12 mutant compared to normal MCF10A cells. Oxidized ferrocenemethanol is reduced by glutathione and the resulting maps of current over cell cultures were different for transformed cells compared to normal cells. Furthermore, scanning electrochemical microscopy using ferrocenemethanol redox mediator was able to distinguish human lung carcinoma cells from the surrounding normal epithelium of clinical specimens. We propose that scanning electrochemical microscopy analysis using specific redox mediator such as ferrocenemethanol may become a useful tool in cancer diagnostics.